102k views
2 votes
Factor ^2 - 4x + 4.
x^2 - 4x +4=

Factor ^2 - 4x + 4. x^2 - 4x +4=-example-1

1 Answer

0 votes

Answer: (x-2)(x-2)

This is the same as
(x-2)^2

============================================

Step-by-step explanation:

The middle coefficient is -4 and the last term is 4.

We need to find factors of the last term that add to the middle coefficient.

Here is a list of all ways to multiply two integers to get 4, and the sum of each pair of factors.

  • -1 + (-4) = -5
  • -2 + (-2) = -4
  • 2 + 2 = 4
  • 1 + 4 = 5

The second row of that list above is what we're after. So

-2 + (-2) = -4

-2 * (-2) = 4

Meaning the factorization is (x-2)(x-2). Note the "-2" values in each factor

We can use the FOIL rule or distribution to go from (x-2)(x-2) back to x^2-4x+4 to confirm the answer.

User Sobutterysosmooth
by
5.2k points